GENETIC MANIPULATIONS WITH THE AXL GENE IN BLADDER CANCER CELLS: UNVEILING FUNCTIONS OF TWO MAJOR ISOFORMS - Myrzagali, Sandugash (Nazarbayev University School of Medicine, 2025)
AXL protein is a receptor from the TAM receptor tyrosine kinase protein family, which also includes MERTK and TYRO3. TAM receptors are crucial for the normal functioning of immune cells, but these proteins are expressed by cancer cells too. AXL is important for the promotion of EMT, immune evasion, cell motility and drug resistance development by cancer cells. AXL receptor also regulates the cellular communication between tumor microenvironment and cancer cells either by binding to its ligand Gas6 or independently. The underlying mechanisms include the regulation of immunosuppressive and immunostimulatory cytokines, although the main reason is the activation of survival pathways (Akt, MAPK, PI3K) downstream the AXL. Inhibition of TAM receptors is not toxic for cancer cells and its knockout is also viable, but inhibition of these receptors can sensitize cancer cells against other antimitotic drugs. There is a strong association between the high level of AXL and poor clinical outcome among patients with metastatic cancer, including those with bladder cancer. Worldwide, bladder cancer is one of the common cancer types, which potentially can be targeted through AXL inhibition.
Keywords: Type of access: Embargo